Přípava Grätzelova solárního článku - Gerlich, Jakub (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2015)
Bakalárska práca rieši problematiku farbivami senzibilizovaných solárnych článkov. Práca uvádza princíp fungovania týchto článkov. Ďalej rozoberá použitie rôznych typov farbív, protielektród, elektrolytov a vodivých skiel. Práca obsahuje tiež princípy merania účinnosti solárnych článkov. V práci sa tiež rozoberá spôsob výroby daných článkov. Praktická časť je zameraná na výrobu prototypov článkov a meranie ich parametrov.

This bachelor thesis focuses on the problematic of the dye-sensitized solar cells. The thesis states the working principle of these cells. It also deals with the use of different types of dyes, counterelectrodes, electrolytes and conducting glass. The thesis also contains the principles used in measuring the effectivity of solar cells. The manufacturing process of these cells is described in this thesis. The practical part of the thesis is focused on the manufacture of cell prototypes and the measuring of their parameters.
Preparing of Grätzel solar cell
Keywords: Farbivami senzibilizované solárne články; farbivá; solárne články; Grätzel; Dye-sensitized solar cells; dyes; solar cells; Grätzel